Reconstruction of Law-Making in Indonesia: A Review of Legal Effectiveness - Nasution, Mirza; Saragih, Geofani Milthree; Sulastri, Sulastri; Suaka, Mardhatillah; Sanathana Ishwara, Ade Sathya (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2025)
Ideally, the formulation of laws in Indonesia should align with the principles of a state based on law, emphasizing justice, legal certainty, and utility. However, in reality, the legislative process is often influenced by political interests, weak public participation, and the poor quality of academic manuscripts that fail to support legal effectiveness. This study aims to analyze the weaknesses in the legislative procedure in Indonesia and to offer a more effective conceptual reconstruction so that legislative products truly reflect the will of the people and fulfill the principles of a state governed by law. This article falls under library research with a qualitative approach. The methodology employed is normative legal research. The findings indicate that the effectiveness of law in the legislative process has not yet been optimal due to ongoing political dominance, low-quality public participation, and weak academic foundations. Therefore, the reconstruction of the law-making process should focus on improving the quality of academic manuscripts, strengthening mechanisms for public participation, and consistently applying the principles of transparency and accountability.